Computational fluid dynamics simulation of reactive fine particulate matter in a street canyon. (15th July 2019) - Kim, Minjoong J.; Park, Rokjin J.; Kim, Jae-Jin; Park, Sung Hoon; Chang, Lim-Seok; Lee, Dae-Gyun; Choi, Jin-Young
Abstract: We developed a coupled computational fluid dynamics–chemistry model to examine the transport and chemical transformation of reactive aerosols on an urban street. The model was evaluated by comparing the results of simulations with those of observational campaigns in a street canyon in Elche, Spain. The model generally captured the composition of fine particulate matter (PM1 ) in the street canyon in summer and winter. However, compared with the observed concentration of PM1 in summer, the simulated concentration of PM1 was overestimated by 40%, indicating that the model predicted a weaker canyon vortex. Although the model has some bias, it reasonably reproduced the observed aerosol concentration. We also investigated the diurnal variations and spatial distribution of PM1 and its composition in the street canyon. The simulated sulfate concentrations were mostly affected by boundary transport, showing weak diurnal variations. The nitrate aerosol concentrations exhibited clear sinusoidal diurnal variations following the precursor gas, HNO3, which is mainly formed by photochemical reactions. We also found that nitrate aerosol formation was suppressed by low O3 concentrations under extreme volatile organic compound-limited conditions. The concentrations of PM1, organic carbon, and black carbon followed traffic volume curves, indicating the dominant effect of vehicular emissions on aerosols. Our sensitivity model simulation showed that considering chemical reactions significantly affects the diurnal variations of secondarily produced aerosol concentrations. These results clearly demonstrate that considering chemical production and loss is essential to investigate the diurnal variations of PM1 in street canyons, especially in winter. Highlights: We developed a coupled CFD–chemistry model for reactive aerosols. PM1 followed the variations of carbonaceous aerosols in a street canyon. Low O3 concentrations suppressed nitrate aerosol formation. Considering chemical reactions affects the diurnal variations of aerosol.